Immunogenicity and safety of different combinations involving a third booster dose of SARS-CoV-2 inactivated vaccine, inactivated quadrivalent influenza vaccine, and 23-valent pneumococcal polysaccharide vaccine in adults aged ≥60 years: a phase 4, randomized, open-label study - Bai, Shuang; Zhou, Shanshan; Zhang, Junnan; Chen, Weixin; Lv, Min; Wang, Jian; Zhang, Ao; Wu, Jiang; Zhao, Wei (Frontiers in Immunology, 2024)
Background Concomitant administration of COVID-19, influenza, and pneumococcal vaccines could reduce the burden on healthcare systems. However, the immunogenicity and safety of various combinations of a third booster dose of SARS-CoV-2 inactivated vaccine (CoronaVac), inactivated quadrivalent influenza vaccine (IIV4), and 23-valent pneumococcal polysaccharide vaccine (PPV23), particularly in different age groups, is still unknown. Methods A phase 4, randomized, open-label, controlled trial was conducted in Beijing, China. 636 healthy adults were divided into two age groups (18-59 and ≥60 years) and randomized equally into three groups: CoronaVac and IIV4 followed by PPV23; CoronaVac and PPV23 followed by IIV4; or CoronaVac followed by IIV4 and PPV23, with a 28-day interval between vaccinations. Immunogenicity was evaluated by measuring antibody titers, and safety was monitored. ClinicalTrials.gov Identifier: NCT05298800. Results Co-administration of a third dose of CoronaVac, IIV4, and PPV23 in any combination was safe. Among adults aged 18-59, co-administration with PPV23 maintained non-inferiority of antibody levels for CoronaVac and IIV4, despite a slight reduction in antibody responses. This reduction was not observed in participants ≥60 years. Furthermore, co-administration of IIV4 and PPV23 affected seroconversion rates for both vaccines. Conclusions Co-administration of the third dose of SARS-CoV-2 inactivated vaccine with the influenza vaccine, followed by PPV23, may be optimal for adults aged 18-59. In adults ≥60, all vaccine combinations were immunogenic, suggesting a flexible vaccination approach. Since antibody measurements were taken 28 days post-vaccination, ongoing surveillance is essential to assess the longevity of the immune responses.